Another order on the Battle Banner: Military Academy of Radiation, Chemical and Biological Protection named after Marshal of the Soviet Union S.K. Tymoshenko was awarded the Order of Kutuzov - K. N. Akkuzin; E. A. Chugunov (Вестник войск РХБ защиты)
.